2021
DOI: 10.3390/molecules26123690
|View full text |Cite
|
Sign up to set email alerts
|

Activity Guided Isolation of Phenolic Compositions from Anneslea fragrans Wall. and Their Cytoprotective Effect against Hydrogen Peroxide Induced Oxidative Stress in HepG2 Cells

Abstract: Anneslea fragrans Wall., commonly known as “Pangpo Tea”, is traditionally used as a folk medicine and healthy tea for the treatment of liver and intestine diseases. The aim of this study was to purify the antioxidative and cytoprotective polyphenols from A. fragrans leaves. After fractionation with polar and nonpolar organic solvents, the fractions of aqueous ethanol extract were evaluated for their total phenolic (TPC) and flavonoid contents (TFC) and antioxidant activities (DPPH, ABTS, and FRAP assays). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The leaves of Anneslea fragrans , or “Pangpo Tea”, are traditionally used as an herbal tea for the treatment of liver and intestinal diseases [ 16 , 17 , 18 ]. They have antioxidant and anti-inflammatory effects [ 17 , 18 , 19 ]. Our studies found that CF is a major chemical compound in the leaves of A. fragrans , which may have beneficial antioxidant and anti-inflammatory effects [ 17 , 18 , 19 ], but whether CF has a hepatoprotective effect in liver disease has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves of Anneslea fragrans , or “Pangpo Tea”, are traditionally used as an herbal tea for the treatment of liver and intestinal diseases [ 16 , 17 , 18 ]. They have antioxidant and anti-inflammatory effects [ 17 , 18 , 19 ]. Our studies found that CF is a major chemical compound in the leaves of A. fragrans , which may have beneficial antioxidant and anti-inflammatory effects [ 17 , 18 , 19 ], but whether CF has a hepatoprotective effect in liver disease has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…They have antioxidant and anti-inflammatory effects [ 17 , 18 , 19 ]. Our studies found that CF is a major chemical compound in the leaves of A. fragrans , which may have beneficial antioxidant and anti-inflammatory effects [ 17 , 18 , 19 ], but whether CF has a hepatoprotective effect in liver disease has not yet been explored. In this paper, we were the first to investigate the protective effect of CF against liver injury induced by excessive APAP.…”
Section: Introductionmentioning
confidence: 99%
“…They present antioxidative or targeted oxidative effects of miscellaneous small-molecular-weight compounds or proteins against a variety of cancer types: An endogenous compound—melatonin [ 2 ]. Natural plant compounds (naringenin [ 3 ], papaverine [ 4 ], polyphenols isolated from Myrciaria trunciflora [ 5 ] or Anneslea fragrans [ 6 ], and seed-derived peptides [ 7 ]), natural compounds also found in animals (melatonin [ 2 , 8 ]), and peptides as well as proteins from Jellyfish venom [ 9 ]. Synthetic compounds, i.e., alkyl thiols [ 10 ], dimethyl sulfoxide [ 11 ], metformin and S63845 [ 12 ], the ruthenium complex [Ru(Phen) 3 ] 2+ [ 13 ], and copper-based compounds—Casiopeinas [ 14 ].…”
mentioning
confidence: 99%
“…Natural plant compounds (naringenin [ 3 ], papaverine [ 4 ], polyphenols isolated from Myrciaria trunciflora [ 5 ] or Anneslea fragrans [ 6 ], and seed-derived peptides [ 7 ]), natural compounds also found in animals (melatonin [ 2 , 8 ]), and peptides as well as proteins from Jellyfish venom [ 9 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation